AME evidence series 001 - The Society for Translational Medicine: clinical practice guidelines for diagnosis and early identification of sepsis in the hospital - Zhang, Zhongheng; Smischney, Nathan J.; Zhang, Haibo; Poucke, Sven Van; Tsirigotis, Panagiotis; Rello, Jordi; Honore, Patrick M.; Kuan, Win Sen; Ray, Juliet June; Zhou, Jiancang; Shang, You; Yu, Yuetian; et al. (Journal of thoracic disease, 2016)
Sepsis is a heterogeneous disease caused by an infection stimulus that triggers several complex local and systemic immuno-inflammatory reactions, which results in multiple organ dysfunction and significant morbidity and mortality. The diagnosis of sepsis is challenging because there is no gold standard for diagnosis. As a result, the clinical diagnosis of sepsis is ever changing to meet the clinical and research requirements. Moreover, although there are many novel biomarkers and screening tools for predicting the risk of sepsis, the diagnostic performance and effectiveness of these measures are less than satisfactory, and there is insufficient evidence to recommend clinical use of these new techniques. As a consequence, diagnostic criteria for sepsis need regular revision to cope with emerging evidence. This review aims to present the most updated information on diagnosis and early recognition of sepsis. Recommendations for clinical use of different diagnostic tools rely on the Grades of Recommendation Assessment, Development and Evaluation (GRADE) framework. Because most of the studies were observational and did not allow a reliable assessment of these tools, a two-step inference approach was employed. Future trials need to confirm or refute a particular index test and should directly explore relevant patient outcome parameters.